Metodologi Pemikiran Fazlur Rahman Dalam Memahami Hadits: Menjembatani Konteks Historis Dan Relevansinya Di Era Kontemporer - Muhammad Umar Ibnu Malik (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
In the current era, traditional and fundamental understanding of hadith may not be enough to answer the challenges of problems in the contemporary era, so in this context a contextual and relevant approach to problems is needed in a holistic and comprehensive manner. This article aims to elaborate and analyze in depth the concepts of understanding hadith initiated by Fazlur Rahman historically, contextually, and their relevance in the contemporary era. This research uses historical methods by collecting book literature, journals, articles, then criticizing all existing literature, and analyzing it to create an article. The research findings show that the socio-historical approach uses a regressive model which includes macro asbabul wurud related to social, psychological, geographical, political, anthropological, historical conditions and matters related to the decline of hadith. Emphasizing the ideal-moral concept, the movement is referred to as a progressive movement with a scheme of taking into account the situation and conditions of the macro and micro context, also determining moral goals from macro and micro responses, as well as adapting moral-social goals to the current context. This phenomenon, which Rahman calls the